Conceptual Modelling to Assess Hydrological Impacts and Evaluate Environmental Flow Scenarios in Montane River Systems Regulated for Hydropower. (15th August 2014) - Geris, J.; Tetzlaff, D.; Seibert, J.; Vis, M.; Soulsby, C.
Abstract: To improve understanding of natural and managed flow regimes in data‐sparse regulated river systems in montane areas, the commonly used Hydrologiska Byråns Vattenbalansavdelning (HBV) conceptual run‐off model was adapted to incorporate water regulation components. The extended model was then applied to the heavily regulated river Lyon (391 km 2 ) in Scotland to reconstruct the natural flow regime and to assess the impacts of regulation at increasing spatial scales. Multi‐criteria model evaluation demonstrated that the model performed well in capturing the dominant catchment processes and regulation effects, especially at the timescales at which operation rules apply. The main change as a result of regulation in the river Lyon is a decrease in inter‐annual and intra‐annual variability of all elements of the flow regime, in terms of magnitude, frequency, and duration. Although these impacts are most pronounced directly downstream of the impoundments, the regulation effects propagate throughout the river system. The modelling approach is flexible and widely applicable and only limited amounts of data are required. Moreover, results are easily communicated to stakeholders. It has the potential to contribute to the development of flow regimes that may be more beneficial to the ecological status of rivers. In the case of the river Lyon, it is likely that this involves a more variable release regime. The approach developed here provides a tool for assessing impacts on flow regimes and informing environmental flows in other data‐sparse regions with heavily regulated montane river systems. Copyright © 2014 John Wiley & Sons, Ltd.